(untitled) (LACCEI, 2024)
The purpose of this research focuses on the design of an instrument to measure the level of appropriation of soft skills, of the final students of the Technological University of Bolívar (UTB). The study aims for the validation of said instrument so that a reliable and effective tool is provided for Higher Education institutions. The study presented in this publication is exploratory in nature and used a cross-sectional qualitative research design. A preliminary instrument was designed, which was subjected to review processes through descriptive, correlation and inferential statistical analyses, which allowed establishing the determining dimensions and questions, in order to measure the appropriation of the defined soft skills. Based on the above, a reliable instrument is provided, to the existing gap in the supply of this type of evaluation instruments, which can be decisive in the search for evaluative elements that guarantee that the training in soft skills in the institutions of higher education, is being appropriated by its graduates.